Modelling and simulation of damage mechanisms in railway vehicle-track interaction. Issue 1 (September 2020) - Ciuffini, F; Favo, F; Giulianelli, S; Miele, A; Sitongia, G R; Strano, S
Abstract: This paper focuses on the estimation of damage contribution that each type of railway vehicle produces on the line Pescara - Ancona. The results of the numerical simulations provides fundamental information to understand the railway vehicle properties mostly influencing track damage mechanisms. The results have clearly shown the influence of the wheelset vertical forces on the damage indicators. The analysis of the specific contribution on damage by a specific railway vehicle will be particularly important to modulate track access charges by vehicle type. Moreover, simulation results will allow to adjust the unit maintenance cost of the line on the class of train, whose volumes are known.